Home Automation With Blynk And Nodemcu - et. al., Dr. Venkateshappa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The need for conservation of energy is very high in demand due to rise in population and consumption of energy.The main reason of energy loss is due to no access and control over the appliances remotely. AnApp or web application is employed by user to offer instruction to those systems. This system can make use of a number of communication method like Bluetooth, Wi-Fi, Zigbee, GSM.Different configurations and controlling devices are often discovered in the existing system. These systems are there in many place for a good sort of reasons and application. In this paper,there is a studyof related systems.